1985
DOI: 10.1007/bf02534772
|View full text |Cite
|
Sign up to set email alerts
|

Purification of the human anionic polypeptide fraction of the apo‐bile lipoprotein complex by zonal ultracentrifugation

Abstract: The two main proteic constituents of the human Apo-bile lipoprotein complex (BLC), i.e., the anionic polypeptide fraction (APF) and the IgA fragments, were separated by preparative zonal ultracentrifugation using a sucrose gradient containing 1.5 mM glycodesoxycholate. The purification of the APF was verified by sodium dodecyl sulphate (SDS) polyacrylamide gel electrophoresis and immunology, and its amino acid composition then was determined. This procedure was used to obtain a polyclonal antiserum directed so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The studies of Lafont et al and Ostrow et al have independently found the same anionic calcium‐binding protein to be present in bile: a LMW acidic glycoprotein (MW approx. 10 kDa) isolated from hepatic bile, gallbladder bile, cholesterol gallstones, and pigment stones []. Shimizu et al [9] also isolated a LMW acidic glycoprotein capable of inhibiting the precipitation of calcium carbonate in a supersaturated solution; this proved to be the same protein as that reported by Lafont et al and Ostrow et al [] and it promoted nucleation in lithogenic bile.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The studies of Lafont et al and Ostrow et al have independently found the same anionic calcium‐binding protein to be present in bile: a LMW acidic glycoprotein (MW approx. 10 kDa) isolated from hepatic bile, gallbladder bile, cholesterol gallstones, and pigment stones []. Shimizu et al [9] also isolated a LMW acidic glycoprotein capable of inhibiting the precipitation of calcium carbonate in a supersaturated solution; this proved to be the same protein as that reported by Lafont et al and Ostrow et al [] and it promoted nucleation in lithogenic bile.…”
Section: Discussionmentioning
confidence: 97%
“…10 kDa) isolated from hepatic bile, gallbladder bile, cholesterol gallstones, and pigment stones []. Shimizu et al [9] also isolated a LMW acidic glycoprotein capable of inhibiting the precipitation of calcium carbonate in a supersaturated solution; this proved to be the same protein as that reported by Lafont et al and Ostrow et al [] and it promoted nucleation in lithogenic bile. Proteolytic fragments and polymeric forms derived from Opn have also been recognized in bile, including a functional arginine–glycine–aspartate (RGD) cell‐binding domain.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sccretion of bile salts into bile leads to the formation of lipoprotciri vesicles (BLC) able to transport free cholesterol and phospholipids (7). These vesicles are stabilized by a major anionic apoprotcin called APF closely associated with bile lipids in bile.…”
Section: Discussionmentioning
confidence: 99%
“…In BLC, biliary lipids are closely associated with a small, heat-stable, acidic amphipathic apoprotein called anionic polypeptide fraction (APF), with tightly bound bilirubin (7). In human bile, APF was recently purified by zonal ultracentrifugation, and polyclonal and monoclonal antibodies were obtained (8).…”
mentioning
confidence: 99%